The status of elephants in Kasungu National Park, Malawi, in 2003 - Bhima, Roy; Howard, James; Nyanyale, Samuel (Pachyderm, 2003)
A dung count was used to assess the density of elephant in two separate areas (north, and central/southern) of the Kasungu NP, Malawi and attempted to determine the extent of elephant poaching and the steps needed to ensure protection of the remaining population. Dung survey results suggest a population of 120-177 elephant occupies the southeastern portion of the Park. No elephant or recent signs of their presence were noted in the northern sector. This illustrates a significant population loss over the last two decades: 1975-1978 over 2000 elephant in Kasungu, 1992 approximately 900, 1996 about 321, and presently less than 200. (Jachmann and Bell 1978: Mkanda 1992, Bhima 1996). Poaching is the prime cause of this loss. Reviews present guard numbers and workload as well as backgound of law enforcement, and concludes that population loss will continue unless law enforcement activities are sufficiently increased to control poaching.